A interação linguageira dentista-paciente na atividade de trabalho em triagem de clínica odontológica - Otranto, Maria Inês Sarno (2006)
This research aims to analyse the genre of activity of the dentist, considering it as a work activity / service relationship, and presuming that the humanized attendance care meaning effect starts building itself during the dialogic interaction activity in the first consultation. The research data were collected at the Triage Room of the dental clinic of a professional improvement school, in São Paulo. The research justifies itself because, now-a-days, there is a social demand for the humanized care for the dental patient whith the dentist following the techno-professional prescriptions of his work (i.e. taking care of, promoting oral health and preventing bucal diseases) and of the Dental Ethic Code, but also being aware of the comunicative interaction with the patient. In this sense, the text/context relationship will be established, considering the discursive memory relating the dental and the medical professions. For the analysis of the data corpus various theories and methodologies were used, as ergologics (Schwartz), the psychology of the work as seen by the Activity Clinic (Clot) and self-confrontation (Faïta), work disciplines; the dialogism concept (Bakhtin) and the french enunciative-discoursive discourse analysis (Maingueneau), language theories; and the french group Language and Work conceptions and contribuitions about the meaning co-construction during interaction in the activity (Boutet, Lacoste, Grosjean). The methods used for the research data construction were interviews, field booknotes, audio recordings and self-confrontation. The research outcome, despite the fact that only one social actor was analysed, points out to a possible conclusion that during his work activity the dentist can be as ethical as professionally required and promote a humanized attendance, when creating conditions to the other the patient, to express his voice